Building the Concept of Corporate Social Responsibility Concept Based on Shari'ate Enterprise Theory - Ugroseno Damara Prasadhana Handoyo; Iwan Triyuwono; Aji Dedi Mulawarman (Sekolah Pascasarjana Universitas Brawijaya, 2019)
Corporate Social Responsibility (CSR) is an acknowledgment of the company that their business activities have an impact on society and the environment, and the impact is used as a reference by management in business decision making (Hughes and Kapoor, 1985). This research will be aimed to reconstruct CSR concept using shari'ate enterprise theory (SET) perspective. The CSR conceptions criticized in this study are the principles of CSR. This principle will be focused on the principles that developed by International Organization for Standardization with the concept made by the institution on CSR, namely ISO 26000. The methodology used in this research is qualitative methodology based on critical paradigm, so this research try to critically examine the concept when viewed from Shari'ate enterprise theory (SET). By using Shari'ate enterprise theory, this study is expected to be able to liberate, change the principles of CSR based on ISO 26000 and seek other alternatives, namely the principles of CSR in shariah construction. Thus, it can be used to reduce the limitations of previous CSR based on ISO 26000 principles and to be able to find solutions to the social problems that are occurring within the principles of CSR base on ISO 26000. These values, including: the value of justice, the value of trust (amanah) and the value of responsibility. The result of reconstruction as the final result in this research is the principles of CSR based on ISO 26000 into CSR in shariah construction.